Optimizing Sustainability in High-Speed Rail Rolling Stock through CFRP Material Substitution - Rungskunroch Panrawee; Maneerat Patcharaporn (E3S Web of Conferences)
This research investigates the environmental and operational advantages of replacing traditional materials in high-speed rail (HSR) rolling stock components with advanced composite materials. By substituting key parts—such as the roof, door, car body, brake control unit, braking rheostat, and bogie transom—with glass-filled epoxy, polyester, and nylon, the study achieves a significant reduction in rolling stock weight by 24.61%. This weight reduction contributes to lower energy consumption and reduced CO2 emissions. Additionally, the recyclability and recoverability rates of these composite materials show marked improvements, reaching 73.9% and 78.9%, respectively, compared to 61.4% and 73.1% in the conventional model. The findings demonstrate that integrating composite materials can enhance the sustainability and efficiency of HSR systems by minimizing landfill waste and operational emissions. This study provides a foundational approach to using lightweight, recyclable materials in rail transportation, with promising implications for future sustainable developments in the industry.